Thinking through ACAD - learning to see theory in action - Castañeda, Linda; Yeoman, Pippa; Carvalho, Lucila; Green, Jenny; Esteve-Mon, Francesc (Proceedings of the International Conference on Networked Learning, 2024)
The Activity-Centred Analysis and Design (ACAD) has been developed as a meta-theoretical framework for understanding and improving complex networked learning situations (Goodyear et al., 2021; Goodyear & Carvalho, 2014). ACAD helps to foreground two distinct moments related to the design of complex learning situations. The first entails advanced planning – and it involves design time – when an educator may consider the selection of specific tasks, tools, and complementary social arrangements of a learning situation. The second involves learning time – or what happens as a learning activity unfolds. When designing for networked learning educators need to anticipate a certain form of human activity and consider how designable elements may influence what students do (first view). But educators also need to channel what actually happens on the day, as activity unfolds, noticing how designable elements influence (or not) the intended learning activity (second view). One difficulty for teachers or educational designers relates to being able to draw connections between what has been designed (planned) and what learners actually do (learn).